A Critical Discourse Analysis of Donald Trump’s Rhetorical Animosity Against Illegal Immigrants - Aperocho, Maico Demi B.; Ates, Lois Alyanna Casilac; Corias, Dona Bella Ponce (Future Science / FSH-PH Publications, 2022)
This study looked at the discourses used by former U.S. President Trump against immigrants. Specifically, the rhetorical expressions, metaphorical approaches, semantic expressions, linguistic features, and classifications of ideologies in the political discourses were explored. Findings show that the discourses contained various rhetorical expressions and discourse patterns in his political speeches. With the use of conceptual metaphor theory for analysis, it showed that he expressed racism against immigrants and immigration and his political speeches also contained pieces of evidence of negative rhetorical expressions towards illegal immigrants. Findings show that the discursive components could be very instrumental in determining how politicians or leaders express their political ideologies on the issue of immigration, racism, and other socio-political issues in a country.